Study of the relation between NCPI and CACO indices with autumn precipitation of Southern Coast of Caspian Sea - Mohammad Saligheh; Mohammad hossein nasserzadeh; Thmineh Chehreara ziabari (تحقیقات کاربردی علوم جغرافیایی)
In this research, the relationship between NCPI and CACO indices with autumn precipitation of Southern Coast of Caspian Sea (SCCS) was investigated. In this regard, two sets of data were used (Aphrodite and Station). And the days with more rainfall than long-term average rainfall station and on condition that the rainfall is more than 70% of the region rainfall, were chosen as a day of widespread rainfall. The sea level pressure data was extracted and by cluster analysis and coalition method was clustered. Then, a representative of the widespread precipitation days from station dataset was selected, investigated and analyzed accordingly. The results state that within all patterns there exists a high pressure on the upper side of the Caspian Sea, or a margin of high pressure is extended on to the sea itself. These high pressure regions have relatively cold nature that can cause currents in the northern direction while intersecting with the relatively warm water during the summer. These currents can absorb moisture during their motion towards south which can lead to their instability. In addition, one should not forget the fact that in each three investigated patterns, dynamic factors at high levels have intensified the abovementioned phenomenon and enhanced the instability, which as a result brought about widespread precipitation. Continuously, the abovementioned Remote bond indices were extracted on a daily basis and their relation to north coast widespread rainfalls was studied, which came to a meaningful relationship between these index sets and fall index sets. The relationship is direct with NCPI or surveyed stations, and it’s an inverse relationship with CACO. On the other hand, the study of indexes anomalies on the days without rainfall and with rainfall was done by One Way ANOVA and Tukey test. The result was a meaningful index anomaly on the days with and without rainfall.